2016
DOI: 10.5194/bg-13-795-2016
|View full text |Cite
|
Sign up to set email alerts
|

Improved end-member characterisation of modern organic matter pools in the Ohrid Basin (Albania, Macedonia) and evaluation of new palaeoenvironmental proxies

Abstract: Abstract. We present elemental, lipid biomarker and, in the supplement, compound-specific isotope (δ13C, δ2H) data for soils and leaf litter collected in the catchment of Lake Ohrid (Albania, Macedonia), as well as macrophytes, particulate organic matter and sediments from the lake itself. Lake Ohrid provides an outstanding archive of continental environmental change of at least 1.2 million years and the purpose of our study is to ground truth organic geochemical proxies that we developed in order to study pas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…This agrees with previous studies from southeastern Europe where C 29 was reported as the most abundant homologue derived from deciduous trees and shrubs, and C 31 as mainly derived from grasses and herbs (Zech et al, 2010;Holtvoeth et al, 2016). A similar good chemotaxonomic discrimination power of the n-alkane pattern has also been reported from other regions, although slight differences in the patterns were observed between the individual regions: Schäfer et al (2016b) found that high amounts of C 31 and C 33 were produced at grassland/herb sites in temperate central Europe, and that sites with deciduous forests/shrubs were mostly dominated by C 27 .…”
Section: N-alkane Patterns In Modern Plants and Topsoilssupporting
confidence: 93%
See 1 more Smart Citation
“…This agrees with previous studies from southeastern Europe where C 29 was reported as the most abundant homologue derived from deciduous trees and shrubs, and C 31 as mainly derived from grasses and herbs (Zech et al, 2010;Holtvoeth et al, 2016). A similar good chemotaxonomic discrimination power of the n-alkane pattern has also been reported from other regions, although slight differences in the patterns were observed between the individual regions: Schäfer et al (2016b) found that high amounts of C 31 and C 33 were produced at grassland/herb sites in temperate central Europe, and that sites with deciduous forests/shrubs were mostly dominated by C 27 .…”
Section: N-alkane Patterns In Modern Plants and Topsoilssupporting
confidence: 93%
“…At the sampling site of topsoil sample 23s, hornbeam trees were only growing in patches and the site is and probably was intensively used for grazing activities. Likewise, Holtvoeth et al (2016) report similar n-alkane distributions from the Ohrid Basin, i.e., a dominance of grass-derived (C 31 ) n-alkanes in the topsoil of a beech forest. Besides vegetation changes, they suggest that the n-alkanes from the grassy undergrowth overproportionally enter the soil, whereas the leaf litter is more mobile and might thus get relocated.…”
Section: N-alkane Patterns In Modern Plants and Topsoilsmentioning
confidence: 69%
“…Supply from the catchment and increased evaporation could have also increased the concentration of Si ions in the epilimnion, which could have promoted diatom productivity. The sensitivity of diatom productivity to increasing Si concentrations in the water column has been clearly shown in leaching experiments of tephras (D'Addabbo et al, 2015) and in high-resolution studies of diatom changes after the deposition of the Y-5 tephra (Jovanovska et al, 2015).…”
Section: Interglacialsmentioning
confidence: 96%
“…It includes lithological description after core opening, measurement of the geophysical properties, and granulometric, geochemical, mineralogical, and rockmagnetic analyses. These analyses are carried out on whole core sections, on split core surfaces, and on discrete samples (see Wilke et al, 2016) and are described in detail in several individual publications (Matzinger et al, 2007;Wagner et al, 2008aWagner et al, , b, 2009Wagner et al, , 2012Belmecheri et al, 2009Belmecheri et al, , 2010Holtvoeth et al, 2010Holtvoeth et al, , 2016Leng et al, 2010;Lindhorst et al, 2010;Matter et al, 2010;Vogel et al, 2010a, b;Francke et al, 2016;Leicher et al, 2016). Dating of the sediment successions was mainly based on radiocarbon dating as well as tephrostratigraphic and tephrochronological work.…”
Section: Laboratory Workmentioning
confidence: 99%